Teachers’ Perceptions of Implementing Innovative Learning Models in Senior High School Mathematics - Vansello, Alan; Farida, Santi; W, Wahyunengsih (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines high school teachers’ views on implementing innovative mathematics learning models using qualitative methods (in-depth interviews and questionnaires). Although teachers’ responses were generally positive, the study identified several challenges: not all materials are suitable, implementation requires more time and resources, and there are gaps in teachers’ understanding and uneven readiness. Therefore, it is essential to carefully consider this study before full adoption.